Teachers’ Reflections on Teaching Mathematics in English: A Consideration for Developing ESP Course - Samosir, Sri Aulia; Yanti, Aprili; Zebar, Abdul; Rafida, Tien (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This research aimed to identify the Reflections done by mathematics teachers when delivering material when teaching mathematics in international schools. The study was conducted at Permata Bangsa Elementary School, which follows the Cambridge Curriculum and involved mathematics teachers from this school. This study used a Qualitative Method. Data were collected through interviews to obtain in-depth insights, and an interactive analysis method was used. The research found that they use the Team teaching method to improve their English fluency by studying from reference books and other print and online sources and working with their fellow teachers. Mathematics teachers actively aim to increase their knowledge related to mathematics through continuous learning, using special applications, book references, and YouTube online materials, attending webinars, exploring educational websites, collaborating with colleagues, and leveraging technology and online resources. The study's findings provide valuable insights for designing ESP courses for mathematics teachers and help teachers better prepare their English competence.